Perancangan User Experience Aplikasi Edukasi Pertanian menggunakan Human-Centered Design - Tri Berlian Novi; Ahmad Afif Supianto; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Agriculture is a livelihood sector for farmers to meet economic needs. Agricultural extension is used to obtain direct education due to the weakness of farmers in technology to access information sources. However, agricultural extension has been temporarily halted due to the corona virus outbreak. This problem requires a new innovative solution in distributing agricultural education, for example by accessing reliable agricultural information sources and being able to discuss with other farmers. This study aims to design agricultural education, media by considering user experience. The design of user experience is needed as a reference in designing solutions in order to obtain results with good levels of success and satisfaction. The method in this research is the Human-Centered Design (HCD) method which involves users in all phases of HCD and is focused on user needs. Evaluation of solution design using usability testing and a system usability scale to 10 respondents. The evaluation results obtained in usability testing show the effectiveness of the complete-rate of 100%; error rate of 0% and an average time efficiency rate of 412 seconds for all tasks. On the usability scale system, the results of the satisfaction level of 78.5% are categorized as well. It can be concluded that the solution design created is successful and comfortable to use by the user.